understand the pythagores theorem and proof
Answers
Answered by
3
The theorem which is used for measuring sides of only a particular triangle, that is, right angled triangle.
Theorem:
(Hypotenuse)^2= (Perpendicular)^2 + (Base)^2
Theorem:
(Hypotenuse)^2= (Perpendicular)^2 + (Base)^2
munjareenkhan:
yes
Answered by
2
⭐⭐hay user here is ur answer⭐⭐
⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️
In a right right triangle the square of hypotenuse is equal to the sum of square of other 2 sides
Given:-
A right angle triangle ABC right angled
at B
to prove that:-
![{ac}^{2} = {ab}^{2} + {bc}^{2} {ac}^{2} = {ab}^{2} + {bc}^{2}](https://tex.z-dn.net/?f=+%7Bac%7D%5E%7B2%7D+%3D+%7Bab%7D%5E%7B2%7D+%2B+%7Bbc%7D%5E%7B2%7D+)
construction:- Draw BD perpendicular AC
proof:- consider a triangle ADB & ABC
![\frac{ad}{ab} = \frac{ab}{ac} \frac{ad}{ab} = \frac{ab}{ac}](https://tex.z-dn.net/?f=+%5Cfrac%7Bad%7D%7Bab%7D+%3D+%5Cfrac%7Bab%7D%7Bac%7D+)
![{ab}^{2} = ad \times ac \: \: \: \: \: \: equation \: (1) {ab}^{2} = ad \times ac \: \: \: \: \: \: equation \: (1)](https://tex.z-dn.net/?f=+%7Bab%7D%5E%7B2%7D+%3D+ad+%5Ctimes+ac+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+equation+%5C%3A+%281%29)
consider triangle ABC & ABC
![\frac{cd}{bc} = \frac{bc}{ac} \frac{cd}{bc} = \frac{bc}{ac}](https://tex.z-dn.net/?f=+%5Cfrac%7Bcd%7D%7Bbc%7D+%3D+%5Cfrac%7Bbc%7D%7Bac%7D+)
![{bc}^{2} = ac \times cd \: \: \: \: \: \: \: \: equation \: (2) {bc}^{2} = ac \times cd \: \: \: \: \: \: \: \: equation \: (2)](https://tex.z-dn.net/?f=+%7Bbc%7D%5E%7B2%7D+%3D+ac+%5Ctimes+cd+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+equation+%5C%3A+%282%29)
adding equation (1)&(2)
we get
![{ab}^{2} = ad \times ac \: {ab}^{2} = ad \times ac \:](https://tex.z-dn.net/?f=+%7Bab%7D%5E%7B2%7D+%3D+ad+%5Ctimes+ac+%5C%3A)
![{bc}^{2} = ac \times \: cd {bc}^{2} = ac \times \: cd](https://tex.z-dn.net/?f=+%7Bbc%7D%5E%7B2%7D+%3D+ac+%5Ctimes+%5C%3A+cd)
ab^2+bc^2=ac×ad+ac×cd
ab^2+bc^2=ac(ad+cd)
ab^2+bc^2=ac×ac
ab^2+bc^2=ac^2
therefore
AC^2=AB^2+BC^2
--------------------------------------
✔✔✔✔✔✔✔✔✔
I hope it will helpful for u and please mark mee brainlist or follow me plz.....plz....plz
@badboy❤❤
⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️⬇️
In a right right triangle the square of hypotenuse is equal to the sum of square of other 2 sides
Given:-
A right angle triangle ABC right angled
at B
to prove that:-
construction:- Draw BD perpendicular AC
proof:- consider a triangle ADB & ABC
consider triangle ABC & ABC
adding equation (1)&(2)
we get
ab^2+bc^2=ac×ad+ac×cd
ab^2+bc^2=ac(ad+cd)
ab^2+bc^2=ac×ac
ab^2+bc^2=ac^2
therefore
AC^2=AB^2+BC^2
--------------------------------------
✔✔✔✔✔✔✔✔✔
I hope it will helpful for u and please mark mee brainlist or follow me plz.....plz....plz
@badboy❤❤
Attachments:
![](https://hi-static.z-dn.net/files/de4/deae96c42cffa479cd825ca6653a23db.jpg)
Similar questions